Introduction to the Special Issue on Eating Disorders and Obesity in Children and Adolescents - José I. Baile (MDPI AG, 2021)
In this Special Issue of Children, we can find several articles that present the results of various current investigations in the field of eating disorders and obesity in children and adolescents [...]